Toilet Training Sebagai Pembentuk Kemandirian Anak Usia Dini Melalui Kolaborasi Orang Tua dan Sekolah - Apriyansyah, Chandra; Wijiati, Wijiati; Priyanti, Nita (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2025)
This study explores the role of parents in fostering children’s independence through toilet training in early childhood education programs. The research aims to analyze how parental involvement, collaboration with teachers, and environmental factors influence the success of toilet training among children aged 4–6 years. A qualitative descriptive method was used, involving in-depth interviews, classroom observations, and documentation at several PAUD institutions in Bekasi. Data were analyzed through thematic coding and triangulation to ensure validity. The findings reveal four major themes: (1) daily routines and consistency in toilet training help children develop self-control and autonomy; (2) collaboration between parents and teachers strengthens consistency of practices across home and school; (3) supportive physical environments and emotional encouragement significantly enhance children’s readiness; and (4) successful toilet training contributes to broader aspects of independence, confidence, and social interaction. The study also identifies inhibiting factors such as inadequate facilities, differing home–school routines, and limited teacher–child ratios. These findings align with Erikson’s psychosocial theory of autonomy versus shame and doubt and Bronfenbrenner’s ecological systems theory, which emphasize the role of consistent microsystem interactions in early development. The study concludes that successful toilet training is not merely a physical skill but a foundational process in building children’s autonomy and emotional regulation. The implications suggest that early childhood institutions should integrate toilet training into their independence curriculum, strengthen parent–teacher collaboration, and ensure child-friendly facilities.